2005
DOI: 10.1161/01.atv.0000183728.14712.d8
|View full text |Cite
|
Sign up to set email alerts
|

An Unsuspected Metabolic Role for Atrial Natriuretic Peptides

Abstract: Abstract-In normal and obese humans, lipid mobilization and systemic nonesterified fatty acid levels are thought to be acutely controlled by catecholamines (ie, epinephrine and norepinephrine) and insulin. Natriuretic peptides (NPs) are known to play a key role in the regulation of salt and water balance and blood pressure homeostasis. They are involved in the pathophysiology of hypertension and heart failure. (ATP III). The NCEP definition of the metabolic syndrome includes 3 or more of the following: abdomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(28 citation statements)
references
References 124 publications
3
23
0
Order By: Relevance
“…Consistent with prior experimental observations [12], we found that there is a strong relationship between serum NT-proBNP and plasma triglycerides, high density lipoprotein cholesterol, and low density lipoprotein cholesterol levels, suggesting a strong relationship between NT-proBNP and lipid metabolism. An inverse relationship between serum NT-proBNP and cholesterol has been described previously and has been hypothesized to be a potential link impairing the natural blood pressure regulation [6].…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with prior experimental observations [12], we found that there is a strong relationship between serum NT-proBNP and plasma triglycerides, high density lipoprotein cholesterol, and low density lipoprotein cholesterol levels, suggesting a strong relationship between NT-proBNP and lipid metabolism. An inverse relationship between serum NT-proBNP and cholesterol has been described previously and has been hypothesized to be a potential link impairing the natural blood pressure regulation [6].…”
Section: Discussionsupporting
confidence: 92%
“…37 The natriuretic peptide system also influences lipid and glucose metabolism and homeostasis, further potentially contributing to the prognostic value of BNP. 3841 …”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is of interest to note that calorie restriction promotes muscle mitochondrial biogenesis in rodents [106] as well as humans [107] by increasing the levels of nitric oxide, the upstream activator of cGMP/cGK1 pathway. Emerging evidence suggests that natriuretic peptides control lipolysis and lipid mobilization in physiological and pathological conditions [108]. Further supporting the protective effect of natriuretic peptides against obesity, Sengenés et al [92] reported that cardiac natriuretic peptides induce strong lipolysis in isolated human fat cells by producing cGMP via the NPR-A receptor.…”
Section: Adipose Tissuementioning
confidence: 99%